2007
DOI: 10.1007/s00294-007-0164-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a minimal cre1 promoter sequence promoting glucose-dependent gene expression in the β-lactam producer Acremonium chrysogenum

Abstract: The promoter of the cre1 gene, encoding the glucose-dependent regulator CRE1 from the beta-lactam producer Acremonium chrysogenum, carries 15 putative CRE1 binding sites (BS1 to BS15). For a detailed analysis, we fused cre1 promoter deletion derivatives with the DsRed reporter gene to perform a comparative gene expression analysis. Plate assays, Northern hybridizations, and spectrofluorometric measurements of DsRed identified the minimal D4 promoter sequence that promoted glucose-dependent expression. Truncate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Cre-binding sites are found in the promoters of cre genes from diverse filamentous fungi. 171 The promoters of many glucose-repressible target genes have Cre-binding consensus sequences. 172 The Cre1 protein (from the cre1 gene) sequence shows high similarity to other glucose-repressor proteins from filamentous fungi, suggesting a similar regulation and a related role in CCR.…”
Section: Carbon Source Regulation Of Secondary Metabolism Biosynthesimentioning
confidence: 99%
See 4 more Smart Citations
“…Cre-binding sites are found in the promoters of cre genes from diverse filamentous fungi. 171 The promoters of many glucose-repressible target genes have Cre-binding consensus sequences. 172 The Cre1 protein (from the cre1 gene) sequence shows high similarity to other glucose-repressor proteins from filamentous fungi, suggesting a similar regulation and a related role in CCR.…”
Section: Carbon Source Regulation Of Secondary Metabolism Biosynthesimentioning
confidence: 99%
“…172 The Cre1 protein (from the cre1 gene) sequence shows high similarity to other glucose-repressor proteins from filamentous fungi, suggesting a similar regulation and a related role in CCR. Janus et al 171 identified a 114-bp minimal promoter with two Cre1-binding sites, the first minimal regulatory promoter sequence for the b-lactam antibiotic-producing fungus. The identification of 114-bp CT-rich sequences in the nontranscribed cre1 upstream region suggests that it is required to trigger glucosedependent gene expression.…”
Section: Carbon Source Regulation Of Secondary Metabolism Biosynthesimentioning
confidence: 99%
See 3 more Smart Citations